2016
DOI: 10.1016/j.expneurol.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous tissue damage induces long-lasting nociceptive sensitization and regulation of cellular stress- and nerve injury-associated genes in sensory neurons

Abstract: Tissue damage is one of the major etiological factors in the emergence of chronic/persistent pain, although mechanisms remain enigmatic. Using incision of the back skin of adult rats as a model for tissue damage, we observed sensitization in a nociceptive reflex enduring to 28 days post-incision (DPI). To determine if the enduring behavioral changes corresponded with a long-term impact of tissue damage on sensory neurons, we examined the temporal expression profile of injury-regulated genes and the electrophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…The susceptible small-diameter neurons have created further challenges in distinguishing the contributions made by changing intracellular signaling molecules. Although ATF3 upregulation was injury-inducible33 and cell type specific,33,34 the responses of the neuronal soma in patients with DPN, which contributed to neuropathic pain through modulated intracellular signaling molecules, remain ambiguous. The co-upregulation of ATF3 and p-PKCε determined the degrees of neuropathic behavior, and the linear analyses strengthened the molecular significance of p-PKCε.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptible small-diameter neurons have created further challenges in distinguishing the contributions made by changing intracellular signaling molecules. Although ATF3 upregulation was injury-inducible33 and cell type specific,33,34 the responses of the neuronal soma in patients with DPN, which contributed to neuropathic pain through modulated intracellular signaling molecules, remain ambiguous. The co-upregulation of ATF3 and p-PKCε determined the degrees of neuropathic behavior, and the linear analyses strengthened the molecular significance of p-PKCε.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated modification of PGP 9.5 axonal nerve terminals and neuro-immune-endocrine cells in the skin during chronic cutaneous neuroinflammation [ 19 ]. Those abnormalities provide induction of molecular changes, which in advanced skin lesions might resemble immune-mediated tissue injury and engage psoriatic keratinocytes in transmission of itch [ 20 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms remain largely unknown. Rau et al demonstrated that ATF-3 expression was a strong predictor of single cells displaying pain-related electrophysiological properties in a cutaneous tissue damage model [ 32 ]. The decrease of ATF-3 expression in DRG neurons by silencing of TNF-α was associated with the amelioration of mechanical allodynia after L5 spinal nerve transection [ 33 ].…”
Section: Discussionmentioning
confidence: 99%